1998
DOI: 10.1093/oxfordjournals.aje.a009577
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Hemoglobin Measured at Different Times in Pregnancy to Preterm Birth and Low Birth Weight in Shanghai, China

Abstract: This paper addresses two questions: 1) What is the relation of hemoglobin in the second gestational month to preterm birth and low birth weight? 2) How does the relation differ when hemoglobin in the fifth or eighth month or the lowest pregnancy hemoglobin are examined in place of first trimester values? These relations were examined prospectively in 829 women from Shanghai, China in 1991-1992. The population was nearly homogeneous by race, parity, antenatal care, and smoking. Rates of birth outcomes were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
126
2
11

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(142 citation statements)
references
References 22 publications
3
126
2
11
Order By: Relevance
“…The prevalence of anemia in our study was similar to previous reports conducted in Korea (Lim and Kim, 1998;Yu et al, 1999) and in Asia (Hui et al, 1995). Anemia or iron deficiency during pregnancy is associated with intrauterine growth retardation, premature birth, low birth weight, increased labor time, higher risk of infection, elevated maternal and prenatal mortality, muscle dysfunction and low physical capacity (Murphy et al, 1986;Lu et al, 1991;Scholl and Hediger, 1994;Singh et al, 1998;Zhou et al, 1998;Yip, 2000). Lone et al (2004) reported the association between low maternal Hb level and Apgar score o5 at 1 min, which is an index of health status of newborn babies.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of anemia in our study was similar to previous reports conducted in Korea (Lim and Kim, 1998;Yu et al, 1999) and in Asia (Hui et al, 1995). Anemia or iron deficiency during pregnancy is associated with intrauterine growth retardation, premature birth, low birth weight, increased labor time, higher risk of infection, elevated maternal and prenatal mortality, muscle dysfunction and low physical capacity (Murphy et al, 1986;Lu et al, 1991;Scholl and Hediger, 1994;Singh et al, 1998;Zhou et al, 1998;Yip, 2000). Lone et al (2004) reported the association between low maternal Hb level and Apgar score o5 at 1 min, which is an index of health status of newborn babies.…”
Section: Discussionmentioning
confidence: 99%
“…Existe una asociación entre el hematocrito/hemoglobina materna, parto prematuro (<37 semanas de gestación), bajo peso de nacimiento (<2.500g) y morbi-mortalidad perinatal [23][24][25][26][27][28][29][30] . Hay evidencias que la asociación entre hemoglobina baja y parto prematuro se da sólo en los dos primeros trimestres de gestación 24,[27][28][29][30] . Por otra parte existe una relación entre la severidad de la anemia y el curso del embarazo.…”
Section: Consecuencias De La Deficiencia De Hierro En El Embarazounclassified
“…Por otra parte existe una relación entre la severidad de la anemia y el curso del embarazo. Zhou et al 28 , en 829 embarazadas, demostraron una asociación entre la severidad de la anemia en el primer trimestre y el riesgo de bajo peso de nacimiento y parto prematuro. El riesgo de parto prematuro aumentó en 1,6 veces con hemoglobina entre 10g/dL y 10,9g/dL, en 2,6 veces con hemoglobina entre 9g/dL y 9,9g/dL y en 3,7 veces con hemoglobina entre 6g/dL y 8,9g/ dl.…”
Section: Consecuencias De La Deficiencia De Hierro En El Embarazounclassified
“…A nationwide survey in China indicated that iron-deficiency anaemia is higher in the third trimester than earlier in pregnancy (16) . Anaemia in the first and second trimesters, but not in the third, is associated with low birth weight, preterm delivery and stillbirths (16)(17)(18) .…”
mentioning
confidence: 99%